Bagaimana Cara Menangani Judi Online di Masyarakat? - Maya; Nur Asiah; Regina Widi Astrian; Sania Rumatiga; Fatimah Wardatul Jannah (FEBI UIN Sunan Kalijaga, 2024)
The issue of gambling in Indonesia is a complex and challenging one to address, particularly given the prevalence of the practice, which is especially prevalent in the form of online gambling, which is growing rapidly in tandem with technological advances. Despite the implementation of legal measures, such as the arrest of perpetrators and bookmakers, public awareness of the dangers of gambling remains limited. It is therefore imperative that the government implement more robust measures to combat online gambling. This research employs a qualitative interview method with five informants to gain a comprehensive understanding of the issues involved, as well as to analyze data from various sources regarding social issues related to gambling. In accordance with the stipulations set forth in Law Number 9 of 1981 concerning Gambling Control, all forms of gambling, whether conducted within the confines of casinos or via online platforms, are explicitly prohibited. Furthermore, the license to operate these gambling activities has been revoked as of March 31, 1981. This evidence substantiates the assertion that gambling is an unacceptable practice, as it has the potential to give rise to a range of social issues and cause harm to those who engage in it. In response to the prevalence of online gambling, the government has taken several measures, including collaboration with law enforcement agencies, the formulation of pertinent legislation, partnership with the Ministry of Communication and Information, and the imposition of stringent penalties for those involved in online gambling in accordance with Law No. 19 of 2016.